Software quality assurance : a self-teaching introduction. - Chopra, Rajiv (Mercury Learning and Information, 2018)
Using a self-teaching method, this overview of software quality assurance testing contains easy-to- understand chapters with tips and insights about software quality, its basic concepts, applications, and practical case studies. -- Edited summary from book.
Keywords: Computer software -- Quality control.; Computer software -- Testing.; elektronické knihy; electronic books